The Portuguese “Blue Shirts” and Salazar’s “New State” - Pinto, Antonio Costa (2019)
The Portuguese National Syndicalist Movement was founded during the transition to authoritarianism and unified a “political family” which had played an important role in the crises and downfall of the Parliamentary Republic (1911–1926) but had been marginalized during the establishment of stable dictatorial rule under Salazar at the beginning of the 1930s. National Syndicalism belatedly unified fascist currents arising from the large but divided post-war radical right. It attracted the most radical members of the parties and ideological pressure groups created during the twilight years of the Parliamentary Republic. Before it was outlawed and its leaders exiled in the mid-1930’s, National Syndicalism had set up an organization that included a sizeable army sector and had organized several coup attempts against the Salazar regime. As in other authoritarian contexts, the consolidation of the “New State” of Salazar meant the dissolution and repression of native fascism.